Profit Analysis of a System having a sub-system in Fuzzy Environment (International Journal of Engineering and Computer Science, 2019)
This paper presents a reliability model of a system having five units. First the proposed methodology is the assumption of the model. Calculation of parameters like Transition Probabilities, Mean Time to System Failure, Availability of the System and Busy Period of the Repairman comes next. We discuss particular cases by using tools like Fuzzy Theory and Erlangian Distribution. On the basis of above profit analysis is estimated.